Genders, cultures, and literacies : understanding intersecting indentities - Guzzetti, Barbara J. (New York ; Oxon, London : Routledge, 2022)
This volume brings together leading scholars in their fields who offer much needed and wide-ranging perspectives on the intersections of genders, cultures, and literacies. As incidents of racial and gender aggression grow in number and in global attention, it is essential to understand how racial and gender identities and their expressions interplay and influence literacy development and practice. Contributors examine how social identities intersect and are expressed in literacy practices across an array of school and out-of-school settings and discuss how gender and race are represented in individuals' multimodal practices. Chapters address such topics as the literacy practices of incarcerated fathers of color, Black girls' literacies, Indigenous students' cultural literacies, the writing practices of Latinx women for identity representation, and more. Ideal for scholars in literacy studies, gender studies, and cultural studies, this volume is a necessary and original update to the ways cultural, racial, and gender identities are viewed in current educational and sociocultural climates
Section I - Literacies and identities in school settings. -- Section II - Literacies and identities in institutions, agencies, and community settings. -- Section III - Literacies and identities beyond schools, institutions, agencies and community settings
Includes bibliographical references and index.
In English.
Keywords: Sex role; Gender identity; Gender literacy